Buckling Analysis of Steel Semi-Spherical Shells with Square Cutout under Axial Compression - Torabi, H.; Shariati, M. (Проблемы прочности, 2014)
Buckling of steel thin walled semi-spherical shells with square cutout due to axial compressive loads has been studied by numerical simulations, and results were compared with those from the experiments. Выполнены численный расчет потери устойчивости стальных тонкостенных полусферических оболочек с квадратным вырезом, подвергнутых осевому сжатию, и сравнительный анализ полученных расчетных данных с экспериментальными. Виконано числовий розрахунок втрати стійкості стальних тонкостінних півсферичних оболонок із квадратним вирізом, що знаходяться під дією осьового стиску, і порівняльний аналіз отриманих розрахункових даних з експериментальними.